Variasi Morfometri dan Patogenisitas Peronosclerospora spp. Penyebab Penyakit Bulai Jagung di Pulau Jawa, Indonesia - Satriyo Restu Adhi; Fitri Widiantini; Endah Yulia (Jurnal Fitopatologi Indonesia, 2021)
Morphometric and Pathogenecity Variation of Peronosclerospora spp. The Causal Agent of Maize Downy Mildew in Java Island, Indonesia Downy mildew disease in maize caused by Peronosclerospora spp. has been reported to cause yield loss in several production centers in Java. This study aimed to determine the morphometric characteristics and pathogenicity of Peronosclerospora spp.. Ten strains of Peronosclerospora were collected from maize production center in Blitar (BLT), Kediri (KDR), Kediri 2 (KDR2), Klaten (KLT), Cianjur (CJR), Garut (GRT), Jatinangor Sumedang (JTN), Rancakalong Sumedang (RCG), Indramayu (IMY), and Sukabumi (SKB). Morphometric variation was determined using microscope by observing shape of conidium; measuring cell wall thickness, length of conidiophores, dimensions of conidia; and counting the number of branches. Differences in morphology and pathogenicity between strains was evidenced. Dendogram analysis based on morphometric characters differentiated strains of Peronosclerospora into 2 main clusters. One strain, KDR2 is in the same group and identical with reference strain P. philippinensis; while the others are in the same group and identical with reference strain P. maydis. Pathogenicity test showed that IMY strain caused the lowest disease incidence (8.33%) and KLT strain caused the highest disease incidence (47.92%).